2004
DOI: 10.1212/01.wnl.0000118201.89498.48
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in twins

Abstract: The authors were able to apply contemporary classifications to Lennox's twins. The data confirm genetic bases for common generalized epilepsies as well as febrile seizures and provide further support for syndrome-specific genes. Finally, comparable results to our Australian series were obtained, verifying the value of twin studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…2427 Most people with epilepsy, however, have no affected relatives. For example, in a population-based study conducted by our research group, only around 15% of probands with incident epilepsy had one or more first-degree relative with epilepsy.…”
Section: Potential Benefits and Risksmentioning
confidence: 99%
“…2427 Most people with epilepsy, however, have no affected relatives. For example, in a population-based study conducted by our research group, only around 15% of probands with incident epilepsy had one or more first-degree relative with epilepsy.…”
Section: Potential Benefits and Risksmentioning
confidence: 99%
“…Monogenic disorders that cause epilepsy are relatively rare [57]. In contrast, idiopathic generalized epilepsy (IGE) is a polygenic disorder [34, 38, 69, 76, 84]. The first evidence that IGE was a polygenic disorder came from Dr. Lennox’s study of epilepsy in twins [84].…”
Section: Cacna1h Is An Epilepsy Susceptibility Genementioning
confidence: 99%
“…In contrast, idiopathic generalized epilepsy (IGE) is a polygenic disorder [34, 38, 69, 76, 84]. The first evidence that IGE was a polygenic disorder came from Dr. Lennox’s study of epilepsy in twins [84]. He found that even in monozygotic twins there was only a 75% concordance for absence epilepsy, with a 0% concordance in dizygotic twins.…”
Section: Cacna1h Is An Epilepsy Susceptibility Genementioning
confidence: 99%
“…However, the vast majority of the genetic epilepsies are multifactorial, with an underlying genetic contribution that is polygenic, where few or usually none of the susceptibility genes have been identified. This multifactorial concept dates back to the early works of William Lennox [7] and was well established in the modern era with additional twin data [8]. It is important to note that epilepsy with complex genetics and complex epilepsy are distinct concepts.…”
Section: Overview Of Clinical Types and The Genetics Of Epilepsymentioning
confidence: 99%